Effects of blindness and anosmia on auditory discrimination of temperature and carbonation of liquids. (April 2023) - Oleszkiewicz, Anna; Schmidt, Patricia; Smith, Barry; Spence, Charles; Hummel, Thomas
Highlights: Auditory cues are an important source of information about food and drink products. Blind outperform sighted in discriminating sounds of drinks of varying temperatures. Anosmia is related to more accurate auditory discrimination of drink carbonation. These supranormal abilities are likely to develop for adaptative purposes. We demonstrate sensory compensation mechanism in a practical context. Abstract: Our experience of the world around us is multisensory. Although vision is considered the dominant (spatial) sense, attention is increasingly being paid to the importance of auditory cues in navigating behaviour in everyday life. The sounds associated with preparing and consuming foods and drinks have been shown to play an important role in hedonic perception. Yet, little is known about the extent to which auditory cues influence the behavior of blind or anosmic individuals. In the absence of vision, it is likely that more attention is paid to the sounds associated with a certain food or drink items, in order to assess their sensory qualities (e.g., freshness) and help guide their preparation. Product sounds may compensate for the lack of aroma perception in anosmia. We addressed these assumptions by studying a sample of 401 participants of whom 101 were anosmic and 101 were blind. We included two respective control groups with fully functional sensory modalities (sighted: n = 99 and normosmic: n = 100). All of the participants were asked to indicate the temperature and carbonation of drinks based solely on auditory cues. The results of the study indicate that auditory cues are particularly important for the assessment of drink temperature in blind people and carbonation in anosmic individuals. These supranormal abilities likely develop for adaptive purposes. The present study supplements the discussion concerning sensory compensation in blindness, but as one of a few demonstrates this ability in a practical, everyday context of a highly ecological task.